Panama Poverty Assessment : Translating Growth into Opportunities and Poverty Reduction - World Bank (Washington, DC, 2013)
Panama is one of the richest and fastest growing economies in Latin America; however it is considered a country of stark contrasts and, for some of its citizens, abysmal poverty. Large disparities in extreme poverty, poverty, and in other measures of human development exist among its citizens. This chapter examines the trends in economic growth, inequality and poverty in Panama between 1997 and 2008 at both the national level and by region, ethnicity and gender. It presents characterization of the patterns of consumption growth across the consumption distribution (including whether the growth is 'pro-poor'). Next, it examines the role of internal migration flows in explaining shifts in poverty and extreme poverty between rural and urban areas. Lastly, the chapter begins to analyze the inequality of access to basic opportunities among children using the Human Opportunity Index (HOI). The Human Opportunity Index (HOI) is an operational measure of opportunities that takes into account both coverage and the distribution of access to basic goods and services by children, who cannot be held accountable for pre-determined circumstances at birth such as their race, gender, family income, parents' education level, or place of residence. The study is based on nationally-representative Living Standards Measurement Surveys (LSMS), which were conducted in 1997, 2003 and 2008. The LSMS household questionnaire includes quantitative data on various aspects of living conditions, including household structure, housing, infrastructure, health, nutrition, education and training, economic activity (labor), migration, spending and consumption, income, savings, credit, independent business activities, and agriculture. Since the latest available information is for 2008, the poverty numbers presented here reflect the Panamanian situation after the end of the period of high growth but before the impact of the 2008-09 global financial crises. With this latest dataset, there are now three comparable household surveys that allow for the study of the evolution of poverty in Panama between 1997, 2003, and 2008.